Polyethylene microplastics trigger cell apoptosis and inflammation via inducing oxidative stress and activation of the NLRP3 inflammasome in carp gills. Issue 132 (January 2023) - Cao, Jingwen; Xu, Ran; Wang, Fuhan; Geng, Yuan; Xu, Tianchao; Zhu, Mengran; Lv, Hongli; Xu, Shiwen; Guo, Meng-yao
Abstract: Microplastics cause varying degrees of damage to aquatic organisms. Exposure to microplastics contaminated water, the gills are among the first tissues, after the skin, to be affected by microplastics. As an essential immune organ, prolonged stimulation by microplastics disrupts immune function not only in the gills but throughout the body, yet the underlying mechanisms remain elusive. A model of gill injury from exposure to polyethylene (PE) microplastics was developed in this study. H&E staining revealed that polyethylene microplastics caused gill inflammation, vascular remodeling, and mucous cell proliferation. An increase in collagen indicates severe tissue damage. Additional analysis showed that polyethylene microplastics profoundly exacerbated oxidative stress in the gills. TUNEL assay demonstrated cell apoptosis induced by polyethylene microplastic. The mRNA levels were subsequently quantified using RT-PCR. The results showed that polyethylene microplastics increased the expression of the nuclear factor-κB (NF-κB) pathway (NF-κB p65, IKKα, IKKβ) and apoptosis biomarkers (p53, caspase-3, caspase-9, and Bax). Nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) inflammasomes, which is an influential component of innate immunity, were overactive. What's more, the pro-inflammatory factors (TNF-α, IFN-γ, IL-2, IL-6, IL-8, IL-1β) that induce immune disorder also increased significantly, while the anti-inflammatory factors (IL-4, IL-10) decreased significantly. These results suggested that oxidative stress acted as an activation signal of apoptosis triggered by the NF-κB pathway and activating the NLRP3 inflammasome to promote inflammatory immune responses. The present study provided a different target for the prevention of toxin-induced gill injury under polyethylene microplastics. Graphical abstract: Image 1 Highlights: Polyethylene microplastics caused gill injury by inducing oxidative stress. PE-MPS induced intense inflammation and apoptosis in gills. The toxicity of PE-MPS in gills mainly arises from the activation of NF-κB/NLRP3 pathway.